Writing Methods to Create Effective Sentences for Informatics Students of University of AMIKOM Purwokerto - Zulia Karini (IJECA (International Journal of Education and Curriculum Application), 2020)
Dealing with academic activities, students at universities must have skill in writing. However, many students, when going to quote from English reference sources, just copy without paraphrasing first which will result in a high level of plagiarism. Interviews and questionnaires conducted with several students of University of Amikom Purwokerto, class 2018 Informatics study program showed the difficulties they experienced when they wanted to make English sentences. This study aims to describe the difficulty of writing English sentences for students of the Informatics study program, to find out the causes of these errors, and to try to provide alternative solutions to overcome the difficulties faced by students in making English sentences by designing a writing learning method for an effective sentence. This research is a descriptive study, which describes in fact the difficulties experienced by students in understanding English texts. The instrument used in data collection was the English text questions. In this study, the data analysis used consisted of three stages, namely data reduction, data presentation, and drawing conclusions or verification. The results showed that some problems faced by Amikom students in writing English sentences were repeating the words, repeating the phrases, repeating the clauses, and using verbose/wordy sentences. Thus, the writing learning methods were designed, namely: sentence combining, learning techniques to combine sentences, they are compounding, compounding sentence elements, subordinating one clause to another, using appositives to connect ideas, using participial phrases to connect ideas, using absolute phrases to connect ideas.